2019
DOI: 10.1590/1806-9282.65.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid to HDL-cholesterol ratio is a strong predictor of metabolic syndrome in type 2 diabetes mellitus

Abstract: SUMMARY OBJECTIVE Metabolic syndrome (MS) is a clinical entity that associated with increased risk of type 2 Diabetes Mellitus (DM) and cardiovascular diseases. Serum uric acid levels are correlated MS criteria. We hypothesized whether a uric acid to HDL-cholesterol ratio (UHR) could predict diabetic regulation and presence of MS in type 2 diabetic subjects. METHODS Admissions of the subjects with type 2 DM to outpatient clinics of our institution were retrospectively analyzed. Study population grouped int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
83
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(107 citation statements)
references
References 16 publications
1
83
1
2
Order By: Relevance
“…These data agreed with Zeng et al, [12] which reported that UACR was higher in cases with diabetes with nephropathy than in cases with diabetes without nephropathy. Our results disagreed with results of Kocak et al, [13] who reported that there was no considerable difference of statistical significance among the two studied groups in UACR as it has been reported that a decline in the renal function of cases with DM was not always accompanied by an increased UACR.…”
Section: Discussioncontrasting
confidence: 99%
“…These data agreed with Zeng et al, [12] which reported that UACR was higher in cases with diabetes with nephropathy than in cases with diabetes without nephropathy. Our results disagreed with results of Kocak et al, [13] who reported that there was no considerable difference of statistical significance among the two studied groups in UACR as it has been reported that a decline in the renal function of cases with DM was not always accompanied by an increased UACR.…”
Section: Discussioncontrasting
confidence: 99%
“…These proinflammatory muscle growth factors can be induced through autocrine/paracrine manner and cause muscle dysfunction, triggering and sustaining the development of the SO. 33 Moreover, multiple factors in the inflammatory response are closely associated with chronic conditions including obesity, 34 metabolic syndrome, 35 type 2 diabetes 36,37 and coronary heart disease, 38 which all promote to SO. Studies have shown that inflammatory factors are associated with type 2 diabetes, and the increase in white blood cells is mainly due to neutrophil count, while the neutrophil to lymphocyte ratio (NLR) in type 2 diabetes patients is increased compared with the healthy control group.…”
Section: Discussionmentioning
confidence: 99%
“…5 Hyperuricemia has drawn much attention in recent decades, as patients with hyperuricemia often present with metabolic diseases, cardiovascular diseases and cardiometabolic related complications. 6,7 Regarding diabetes, various longitudinal studies have demonstrated that higher baseline levels of serum uric acid increased the risk of developing type 2 diabetes, and a meta-analysis of 11 cohort studies including 42,834 participants indicated a 17% increase in the risk of type 2 diabetes for each 1 mg/dl increase in SUA. [8][9][10] Thus, how uric acid contributes to the pathophysiology of type 2 diabetes deserves research.…”
Section: Introductionmentioning
confidence: 99%